Group II Introns: Mobile Ribozymes that Invade DNA - Lambowitz, Alan M. (Cold Spring Harbor Laboratory Press, 2011)
Group II introns are mobile ribozymes that self-splice from precursor RNAs to yield excised intron lariat RNAs, which then invade new genomic DNA sites by reverse splicing. The introns encode a reverse transcriptase that stabilizes the catalytically active RNA structure for forward and reverse splicing, and afterwards converts the integrated intron RNA back into DNA. The characteristics of group II introns suggest that they or their close relatives were evolutionary ancestors of spliceosomal introns, the spliceosome, and retrotransposons in eukaryotes. Further, their ribozyme-based DNA integration mechanism enabled the development of group II introns into gene targeting vectors (“targetrons”), which have the unique feature of readily programmable DNA target specificity.